ANALISIS KELURUSAN GERAK DAN PEMOSISIAN MEJA MACHINING CENTER MILLAC 4H - Bagiasna, Komang; Darto, Darto (Mesin, 2002)
Accuracy measurements were carried out on a table movement of four axis machining center using laser interferometer based integrated measuring system. In this case the measurements included table positioning accuracy in x-axis direction and table angular as well as table straightness displacement accuracy. Following the obtained results, analysis of the machining center table displacement was carried out by modeling the table accuracy movement using a homogenous transformation matrix (HTM) method. Guide ways deflection was analyzed using five contact point method and other analysis performed by taking into account misalignment between ball screw & slideways. Diagnosis was conducted by comparing the theoretical table accuracy displacement curve and the one obtained from laser interferometer based measurement, for determining the slideways wear contour and the progressive wear of the ball screw.